"\\left( {{D^2} + 4} \\right)y = y'' + 4y = 2{\\rm{cosec}}2x"
Characteristic equation:
"{k^2} + 4 = 0 \\Rightarrow {k^2} = - 4 \\Rightarrow k = \\pm 2i"
Then the general so lution of the homogeneous equation is
"{y_0} = {C_1}\\cos 2x + {C_2}\\sin 2x"
Let
"{C_1} = f(x),\\,\\,{C_2} = g(x)"
Then
"y = f\\cos 2x + g\\sin 2x \\Rightarrow y' = f'\\cos 2x - 2f\\sin 2x + g'\\sin 2x + 2g\\cos 2x"
Let
"f'\\cos 2x + g'\\sin 2x = 0\\,\\,\\,\\,(*)"
Then
"y' = - 2f\\sin 2x + 2g\\cos 2x \\Rightarrow y'' = - 2f'\\sin 2x - 4f\\cos 2x + 2g'\\cos 2x - 4g\\sin 2x"
Substitute the found values ββinto the original equation:
"- 2f'\\sin 2x - 4f\\cos 2x + 2g'\\cos 2x - 4g\\sin 2x + 4f\\cos 2x + 4g\\sin 2x = 2{\\rm{cosec}}2x"
"- 2f'\\sin 2x + 2g'\\cos 2x = 2{\\rm{cosec}}2x"
Together with equation (*) we have the system of equations:
"\\left\\{ \\begin{array}{l}\n - 2f'\\sin 2x + 2g'\\cos 2x = 2{\\rm{cosec}}2x\\\\\nf'\\cos 2x + g'\\sin 2x = 0\n\\end{array} \\right."
From the second equation we obtain
"g' = - f' \\cdot \\frac{{\\cos 2x}}{{\\sin 2x}}"
Substitute the found value into the first equation:
"- 2f'\\sin 2x + 2\\left( { - f' \\cdot \\frac{{\\cos 2x}}{{\\sin 2x}}} \\right)\\cos 2x = 2{\\rm{cosec}}2x"
"- 2f'\\sin 2x - 2f' \\cdot \\frac{{{{\\cos }^2}2x}}{{\\sin 2x}} = \\frac{2}{{\\sin 2x}}"
"- 2f' \\cdot \\frac{{{{\\sin }^2}2x + {{\\cos }^2}2x}}{{\\sin 2x}} = \\frac{2}{{\\sin 2x}}"
"\\frac{{ - 2f'}}{{\\sin 2x}} = \\frac{2}{{\\sin 2x}}"
"f' = - 1 \\Rightarrow f = - x + {C_3}"
"g' = - f' \\cdot \\frac{{\\cos 2x}}{{\\sin 2x}} = \\frac{{\\cos 2x}}{{\\sin 2x}} \\Rightarrow g = \\int {\\frac{{\\cos 2x}}{{\\sin 2x}}dx} = \\frac{1}{2}\\int {\\frac{{d\\sin 2x}}{{\\sin 2x}} = \\frac{1}{2}} \\ln |\\sin 2x| + {C_4}"
Then
"y = f\\cos 2x + g\\sin 2x = \\left( { - x + {C_3}} \\right)\\cos 2x + \\left( {\\frac{1}{2}\\ln |\\sin 2x| + {C_4}} \\right)\\sin 2x"
Answer: "y =\\left( { - x + {C_3}} \\right)\\cos 2x + \\left( {\\frac{1}{2}\\ln |\\sin 2x| + {C_4}} \\right)\\sin 2x"
Comments
Leave a comment